A New Compensation Method for DRR of a Roll-Pitch Seeker Based on ESO - Yue Li; Wei Li; Xiaodong Liu; Qunli Xia (International Journal of Aerospace Engineering)
We propose a new DRR (Disturbance Rejection Rate) compensation method of a roll-pitch seeker based on ESO (extended state observer). The characteristics of a roll-pitch seeker and the DRR definition of two frames of a roll-pitch seeker are analyzed. The influence of different interference torques and different frequency bandwidths on the compensation effect is analyzed. Modeling and simulation of the guidance system of a roll-pitch seeker with the parasitic loop of DRR are carried out. Influence of the new DRR compensation method on dimensionless miss distance is analyzed. Mathematical simulation is established to compare the new ESO-based DRR compensation method with the existing methods such as the feedforward method and Kalman filter method. The analysis and simulation results show that the new ESO-based DRR compensation method has the advantages of high precision, good applicability, and easy adjustment, and the new method can effectively reduce the dimensionless miss distance with different types of input errors. The research of this proposed new method can provide a reference for the latest generation air-to-air missile operations in a high-altitude and high-speed environment and the high-precision research of a roll-pitch seeker.